Platform and method for establishing whole-process metallurgical manufacturing execution system - ZHOU XIANGYANG; XIAO WEI; ZHANG BIAN; LUO TAO; SHI WEI (2015)
The invention discloses a platform for establishing a whole-process metallurgical manufacturing execution system. The platform comprises a business assembly library, an assembly configuring tool, a communication framework, an integrated platform framework and a database, wherein the business assembly library is used for abstracting core manufacturing businesses in a metallurgical enterprise to form business assemblies; the assembly configuring tool is used for performing business object modeling and parameter assignment on the business assemblies in the business assembly library, and generating an assembly configuring file; the communication framework is used for providing a communication service required by the whole system; the integrated platform framework is used for coordinating, assembling and running the configured business assemblies according to the generated configuring file; the database is used for storing user data and system function configuration information, and is an important carrier for data persistence of a system. Through a configurable software platform of the manufacturing execution system, the metallurgical enterprise can achieve establishment and debugging of the manufacturing execution system through the system no matter which manufacturing technique is adopted.